On the excessive functions of the step Markov processes and optimal stopping rules - Grigelionis , B. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Б. Григелионис. Об эксцессивных функциях и оптимальных правилах остановки ступенчатых марковских процессов B. Grigelionis. Apie laiptuotų Markovo procesų ekscesyvines funkcijas ir optimalias sustabdymo taisykles